Formation of innovation human capacity at the enterprises of Kazakhstan Republic - Ramashova, A.N. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article proves the necessity of research of human capacity innovation perspective. The authors present the results of analysis of works by foreign and local scholars on the issue of the formation and development of human potential. It was defined theoretical basis of essence of the concept «innovation». The article presents the role of training human resources capacity, the need to manage human capacity through the existing system. Also the authors attempts distinction between two notions as «human capacity» and «employment potential». It was given original examples of training competitive employee in the field of industrial-andinnovative development of the country, as well as outlines the key competencies required for future specialists. Also the authors studied the experience of Western and Eastern countries in the field of human capacity development, and define the tendencies and prospects of development of the investigated phenomenon.
Қазақстан Республикасы кəсіпорындарында инновациялық кадрлық əлеуеттің қалыптасуы
Формирование инновационного кадрового потенциала на предприятиях Республики Казахстан
Keywords: modernization; innovation; human capacity; market model; innovative activity; competitiveness of labor market; innovative personnel; lifelong learning; management of human capacity; industrial-andinnovative development